Business and tourism high-speed rail same-day trips: factors influencing the efficiency of high-speed rail links for Spanish cities. Issue 3 (4th March 2019) - Moyano, Amparo; Rivas, Ana; Coronado, Jose M.
ABSTRACT: This paper presents an efficiency analysis of high-speed rail (HSR) connections in Spain, focusing on the quality of the services supplied and the friction introduced by all the links of the whole transport chain in same-day trips. The methods proposed consider variations in the efficiency of HSR connections depending first on the different purposes of travel – tourism or business – and second, on the sensitivity of the measure to different transport-related factors such as ticket prices, adequate timetables and local accessibility to/from HSR stations. The results obtained show that large cities in peripheral locations of the network are generally more favoured for business HSR connections, while intermediate cities are more likely to achieve higher efficiency for tourism. Also, the results highlight how for tourism trips, timetables are the key factor in the efficiency measure, while for business, access/egress to/from HSR stations is more relevant. The analysis of the efficiency of HSR connections and its sensitivity to different factors and travel purposes is a useful tool for transport planning, especially for cities, because they may do their best to achieve service quality improvements or even adapt their strategies to different activities.